The Application of Digital Marketing in the Covid-19 Era in the Indonesian Muslim Entrepreneur Association (IPEMI PC Kuranji) Padang City - Meci Nilam Sari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Covid-19 in Indonesia to date has had both positive and negative impacts on the economic sector, especially UMKM in Indonesia. Covid-19 has been felt significantly by Micro, Small and Medium Enterprises UMKM who are experiencing an economic crisis. The research was conducted on Indonesian Muslim women entrepreneurs (IPEMI PC Kuranji) and the impact of covid-19 is the decline in purchasing power of women entrepreneurs IPEMI PC Kuranji because 40% of them are still quoting in the offline world not online, therefore digital marketing is one of the efforts for achievement in improving the business that is more advanced in the future.